Green House and Ḥalāl Budget Allocation for Sustainable Household Finance Realization - Masruroh, Nikmatul; Fadli, Ahmad; Shahrin, Attori Alfi; Fawaid, Yazidul (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2023)
This study explores the formulation of sustainable household financial management through the integration of Green House practices and ḥalāl budget allocation, grounded in Ibn Khaldūn’s social change theory. Employing a qualitative library research method supported by secondary data from national statistics and field observations in Indonesian villages, the study finds that conventional household consumption patterns—driven by overconsumption and digital spending habits—have contributed to both environmental degradation and financial instability. The proposed model promotes financial planning that balances consumption, saving, investment, and charitable giving (zakāh, infāq, ṣadaqah), while integrating eco-conscious practices such as waste banks, Sustainable Food House Areas (KRPL), and Climate Resilient Integrated Service Posts (Postaklim). This research contributes to global Islamic finance and sustainability literature by introducing a maqāṣid al-sharī‘ah-aligned household finance framework that operationalizes ethical budgeting and environmental stewardship. It offers a novel interdisciplinary perspective by combining green economy principles with Islamic economic ethics to promote long-term household financial resilience. The model may serve as a benchmark for international studies aiming to develop culturally contextualized frameworks for sustainable finance at the microeconomic level. Future research could apply this model across diverse socio-economic and cultural settings or test its impact quantitatively on household welfare and environmental outcomes.